Motivation, Learning Strategies, and Outcomes in Mobile English Language Learning - Yu Z. (2023)
An increasing number of studies have been committed to the effectiveness of mobile learning applications. This study examined motivation, learning strategies, learning outcomes, and their mutual correlations in mobile English language learning via two experiments. Results suggested that in mobile English language learning, (a) motivation was significantly stronger than in traditional English language learning; (b) students adopted significantly more learning strategies than in traditional English language learning; (c) learning outcomes were significantly better than in traditional English language learning; and (d) motivation, learning strategies, and learning outcomes were positively correlated in both learning approaches at the significance level.025. Although it is necessary to further identify the underlying mechanisms, findings suggest interdisciplinary cooperation in future research.